Allometry of Organs and the Gastrintestinal Tract from Water Buffaloes (Bubalus bubalis) Finished in Feedlot - Jorge, Andre Mendes [UNESP]; Bonilha Pinheiro, Rafael Silvio [UNESP]; Da Silva, Mauricia Brandao [UNESP]; Francisco, Caroline de Lima [UNESP]; Castilhos, Andre Michel de [UNESP]; Rivaroli, Dayane Cristina [UNESP]; Coutinho, Carolina Cesarino [UNESP]; Prospero Puoli Filho, Jose Nicolau [UNESP] (Int Buffalo Information Ctr, 2013)
The objective of present study was to evaluate the relative growth of organs and viscera from water buffaloes. Fifteen Mediterranean intact males, averaging, 356.7 kg initial live weight and twenty four months of age, were used. The animals were ramdomly assigned into three groups (categories). One group was ramdomly assigned to immediate slaughter (AR), the rest two groups were full-fed a ration containing 50% concentrate, dry matter basis until reaching the slaughter weights of 450 and 500kg, respectively. At slaughter the empty body weight was determined and the weights of head, feet, leather, lungs, heart, liver, spleen, rumen-reticulum, omasum, abomasum, small intestine, large intestine were recorded. Regression equations of log weight of organs and viscera as a function of log empty-body-weight (EBW), were fitted. All body components studied, with exception of liver and spleen, developed slower than in relation to EBW.
Keywords: abomasum; large intestine; omasum; relative growth; rumen reticulum; small intestine